The Hydrated Magnesium Ion Deaquation in Zinc Potassium Sulphate Hexahydrate (Journal of Advances and Scholarly Researches in Allied Education, 2024)
The interatomic distances and angles are listed in Tables-2.1 and 2.2. All water molecules are coordinated to magnesium ions, six to each one. The crystal structure (Fig. 2.2) consists of a packing of these octahedrally hydrated  magnesium ions and unhydrated ammoniums, among the tetrahedral sulphate ions. From the tables it follows that the water octahedra are not regular with their four equatorial bonds being almost equal but greater than the two nearly equal axial (polar) bonds.